Crossing the color line : race, parenting, and culture - Reddy, Maureen T. (Black women writers series., 1994)
"Why do white people have vaginas?" asks Maureen Reddy's two-year-old son. "Why do boys have curly hair?" These are the questions Reddy grapples with on her journey, as a white mother of black children, toward an internalized understanding of race - particularly whiteness - and of racism. Moving from memoir to race theory, to literary analysis, to interviews with friends, Reddy places this personal journey in a broad cultural context. Reddy writes as a racial "insider" who stands outside accepted racial arrangements, a position that can afford unique insight into the many contradictions of those arrangements. She addresses attempts to cross the color line that divides blacks and whites; the meeting points of whiteness and blackness; the politics of feminism and anti-racism; loving blackness; mothering black children; racism in schools; and relationships among black and white women. Our culture is permeated by color. And whether we can sort out racial divisions will, Reddy feels, determine whether we survive as a society